Obstetric Violence: A Challenge in Maternity Care - Chacón, Roberto Enrique Alvarado; Gómez, María Fernanda Morales; Ordoñez, Greta Marisol Vallejo; Vizuete, Elisabeth Germania Vilema (Journal of Advanced Zoology, 2023)
Aim: This research addresses the issue of obstetric violence against women during childbirth. It emphasizes that this violence is deeply rooted in institutional practices and power structures, such as patriarchy. While some countries have legally recognized obstetric violence, there is still a lack of legislation in other places, including Spain. Material and method: The lack of consensus in defining and measuring obstetric mistreatment hinders its study and understanding. The research findings reveal that women experience physical, verbal, and psychological mistreatment during childbirth, leading to anxiety and discomfort. The lack of knowledge about women’s rights during childbirth increases their vulnerability to mistreatment. It is highlighted that obstetric violence is a problem deeply ingrained in the healthcare system and has been normalized by both patients and medical staff. The research underscores the importance of ensuring respect for human rights during childbirth and highlights that obstetric violence constitutes a violation of women’s sexual and reproductive rights. Statistics and Result: The need to work on the relationship between health services and patients to improve the childbirth experience is emphasized. The research concludes that addressing obstetric violence requires a focus on professional training to ensure appropriate and respectful treatment of patients.